Comparative study of ZnS thin films grown by chemical bath deposition and magnetron sputtering - Islam, M. A.; Hossain, M. S.; Aliyu, M. M.; Sulaiman, Y.; Karim, M. R.; Sopian, K.; Amin, N. (2012 7th International Conference on Electrical and Computer Engineering, 2012)
Zinc sulphide thin films have been deposited on FTO coated glass substrates using the sputtering and chemical bath deposition techniques. ZnS thin film is at first grown by CBD using a aqueous solution of thioria, ammonia, ammonium chloride and zinc chloride, respectively; whereas ZnS thin film is also grown from sputtering technique at a substrate temperature 300 °C. The grown films from the both processes were annealed in a vacuum furnace of nitrogen ambient with pressure 250-300 mTorr. A comparative study of structural and optical study of these films was carried out by means of XRD, AFM and UV-Vis spectrometry. It has been found that the films in both processes are polycrystalline in nature having the (200) preferential orientation. The crystallite grain size, lattice constant, microstrain and dislocation densities of the films are quite different in both processes as observed from XRD analysis. Surface structure and topography were observed from the AFM images. The higher r.m.s values of surface roughness as well as bigger grains are observed in CBD grown ZnS thin films. The band gap has been found 3.58 and 3.54eV for the films prepared from CBD and sputtering, respectively.